Empowering Higher Education Funding through Cash Waqf: A Case Study of IPB University - Furqon, Ahmad; Budiman, Achmad Arief; Septiana, Yunita Dewi; Hassane, Narong; Fuadi, Nasrul Fahmi Zaki (Economica: Jurnal Ekonomi Islam, 2022)
This study explores the role of cash waqf as a financial source for universities, focusing on its management and impact at IPB. The institution overseeing cash waqf at IPB operates with principles of good governance, transparency, accountability, and professionalism. Fundraising is conducted both online and offline, with a consistent monthly auto-debit system from faculty and staff salaries. Additionally, IPB actively involves the community in waqf contributions. Investments of cash waqf funds occur in both financial and real sectors, including deposits and cash waqf-linked sukuk in collaboration with BWI. The allocation of cash waqf benefits is executed through direct and indirect mechanisms. Direct benefits include scholarships, community empowerment programs, infrastructure development, research funding, and social responsibility initiatives. Indirect benefits support character development, religious events, Covid-19 care programs, and educational assistance. Furthermore, IPB distributes waqf-generated resources through medical equipment donations, scholarship programs, water station installations, and burial support. These efforts highlight the strategic role of cash waqf in enhancing university sustainability, fostering social welfare, and strengthening educational institutions. The findings emphasize the significance of structured waqf management in optimizing its benefits and ensuring long-term impact within the academic and social domains.